Undergraduate Research Experiences Broaden Diversity in the Scientific Workforce. (7th February 2018) - Hernandez, Paul R; Woodcock, Anna; Estrada, Mica; Schultz, P Wesley
Abstract: New data highlight the importance of undergraduate research experiences (UREs) for keeping underrepresented science students on the pathway to a scientific career. We used a large-scale, 10-year, longitudinal, multi-institutional, propensity-score-matched research design to compare the academic performance and persistence in science of students who participated in URE(s) with those of similar students who had no research experience. Our results showed that students who completed 10 or more hours of cocurricular, faculty-mentored research per week across two or more academic semesters or summers were significantly more likely to graduate with a science-related bachelor's degree, to be accepted into a science-related graduate training program, and to be training for or working in the scientific workforce 6 years after graduation. Importantly, the findings show that just having a URE was not enough to influence persistence in science; it required a commitment of 10 or more hours per week over two or more semesters of faculty-mentored research.